2012
DOI: 10.1542/peds.2011-2962
|View full text |Cite
|
Sign up to set email alerts
|

Physician Attitudes Regarding School-Located Vaccinations

Abstract: Although a majority of Colorado physicians supported influenza and adolescent vaccination at school, they expressed concerns regarding the implications on their practice. Lesser support for vaccination of their privately insured patients and concerns regarding attendance at well-child visits suggests the perceived financial impact from school-located vaccination is a barrier and merits additional examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…In addition, there was stronger support for publicly insured adolescents in the physicians' practices to receive vaccines at school than privately insured patients and significant concerns about the financial repercussions of SLV on the practice were expressed. 40…”
Section: Parental and Provider Attitudes About Slv For Adolescentsmentioning
confidence: 99%
“…In addition, there was stronger support for publicly insured adolescents in the physicians' practices to receive vaccines at school than privately insured patients and significant concerns about the financial repercussions of SLV on the practice were expressed. 40…”
Section: Parental and Provider Attitudes About Slv For Adolescentsmentioning
confidence: 99%
“…Family barriers include time, money, and need for an extra office visit. 8 -11 Experts have discussed schools as sites for influenza vaccination 12 ; most pediatricians [13][14][15] and parents 7, 16 -18 support schoollocated influenza vaccination (SLIV). Additionally, schools have a stake in influenza vaccination because immunization of school-children can reduce absenteeism throughout the community.…”
mentioning
confidence: 99%
“…15 Yet studies to date have shown mixed results for provider and parent acceptance of pharmacies as immunization venues for children. [16][17][18][19] The lack of office visit fees and ease of access have the potential to make pharmacies more attractive to payers and parents. 20 In a time of chronic shortages of primary care providers for adolescents and younger children, encouraging other types of immunization providers and sites is needed from a public health perspective.…”
Section: Discussionmentioning
confidence: 99%